Faktor-Faktor yang Memengaruhi Indeks Pembangunan Manusia di Provinsi Kalimantan Tengah (Jurnal Ekonomi dan Kebijakan Pembangunan, 2018)
During the years between 2010 and 2015, Central Kalimantan’s Human Development Index (HDI) rank has decreased. Its HDI rank is also relatively low if compared to other indicators such as poverty, unemployment, and the gini ratio. This study aims to describe the HDI performance and the factors affecting HDI in regencies / cities in Central Kalimantan. The method used is the panel data regression of 14 regencies / cities in Central Kalimantan from 2010 to 2015. Based on the study results, Seruyan Regency and Pulang Pisau Regency has a low value and growth of HDI. The mean years of schooling index is the lowest index of the HDI components in Central Kalimantan, thus becoming a burden since the new calculation method is using the geometry average. The model results showed that GDP per capita, budgetary allocation for the health, unemployment rate, and dummy regencies / cities have positive effect, while poverty and dependency ratio have negative effect on HDI. The variable that have the greatest influence on the HDI value is GDP per capita. Therefore, the suggested recommendation is to increase GDP by the means of the development of palm oil cluster in Central Kalimantan.